Semangat patriotisme dalam kalangan mahasiswa bukan Melayu di Institusi Pengajian Tinggi sekitar Lembah Kelang - Ku Samsu, Ku Hasnita; Mohd Nor, Mohd Haizam (Universiti Kebangsaan Malaysia, 2009)
Media reports since 2003 have revealed that non-Malay youths especially Chinese and Indians have shown lack of interest in the state defence institutions such as PDRM and ATM which are the main manifestation of patriotism. This situation is said to show lack of patriotism amongst them. Thus, this research is to determine the strength of their patriotism to this country. A total of 743 students had been chosen randomly from two Public Higher Education Institutions (IPTA) and two Private Higher Education Institutions (IPTS) in the Klang Valley. The questionnaire method of survey was utilised in collecting the data for this research, which mainly used the descriptive and the inference statistics analysis. The inference statistic used was the one way test ANOVA, whereas the descriptive statistical method comprised the mean analysis, and percentages. The results show that the level of patriotism is average among non-Malay students. Patriotism amongst respondents was also compared to level of patriotism showed by the American, Canadian, Italian, Thai, Indonesian, Iranian, China and South Korean younger generation.